Evaluation of Subsurface Module Performance in Flow Resistance and Water Quality Improvement - Basri, Muhammad Syahimie (Universiti Teknologi PETRONAS, 2018)
Land use and urbanization are greatly impacting on the natural hydrology and lead to the degradation of storm water quality in receiving waters. Storm water should be properly managed in terms of quantity and quality to enhance sustainable ecosystem. Improvisation of storm water management is expected with the adaptation of newly designed subsurface drainage module by River Engineering and Drainage Research Centre (REDAC) of Universiti Sains Malaysia (USM). In this paper, hydraulic characteristics of the module has been studied in terms of flow resistance and flow attenuation. Manning’s formula has been used to calculate the friction coefficient, n of the subsurface drainage module. Apart from that, the improvement of water quality in terms of dissolved oxygen content has been studied at upstream and downstream position with the presence of the subsurface module.